Scarring of lupus miliaris disseminatus faciei: treatment with a combination of trichloroacetic acid and carbon dioxide laser. Issue 3 (27th November 2013) - Kang, Boo Kyoung; Shin, Min Kyung
Abstract We present a case of a 35‐year‐old man having a 12‐month history of multiple reddish‐brown papules on the chin, forehead, cheeks, and eyelids. Histopathologic findings revealed epithelioid cell granulomas with central necrosis consistent with a diagnosis of lupus miliaris disseminatus faciei. After 9 months of combined treatment with ethambutol, rifampin, and pyrazinamide, most lesions gradually resolved but remained as severe disfiguring scars. After 10 sessions of treatments with 100% trichloroacetic acid and CO2 laser, the lupus miliaris disseminatus faciei scars have been much improved and the patient has never experienced a recurrence of disease during subsequent years of follow‐up.